IMPLEMENTASI DISCOVERY LEARNING PADA IPAS DI KETERBATASAN SARANA DAN PRASARANA - Eka Widiya Lestari; Mulya Budi Harsono, Arta; Suriansyah, Ahmad (PT. Intelek Cendikiawan Nusantara, 2025)
A gap exists between the ideal use of digital media in Discovery Learning and the limited facilities available at SDN Sungai Lulut 7. Using a qualitative case study, this research focused on a third-grade teacher, supported by student data gathered through interviews, observations, and documentation. The findings show that the discovery process can still take place without LCDs or stable electricity by replacing digital media with printed images, real objects, and direct observation activities. Students remained engaged in asking questions, observing, discussing, and drawing conclusions, although challenges like limited media and a crowded classroom were still present. The teacher’s adaptations such as simplifying learning steps, forming small groups, and maximizing simple materials played a key role in keeping the learning process active. These results highlight that the success of Discovery Learning relies more on teacher creativity than technology, offering opportunities for schools with limited facilities to continue meaningful and student-centered learning.